UPAYA PEMERINTAH DAERAH DALAM RANGKA PENCEGAHAN DAN PENANGANAN PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) DI KABUPATEN PANGANDARAN TAHUN 2021 - Arie Budiawan; Sahadi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The purpose of this study is to find out the extent of the efforts made by the Regional Government of Pangandaran Regency in the context of Prevention and Handling of the Covid-19 Pandemic in the Community. Another part is how the supervision that has been carried out by the Regional Government has been running optimally at every level, starting from internal and external monitoring that focuses on encouraging the effectiveness and acceleration of handling COVID-19 in Pangandaran Regency. The method in this research is descriptive qualitative with The aim is to describe the description and explanation of the variables studied. The focus of the research is Local Government Efforts in the context of Prevention and Handling of the Corona Virus Disease 2019 (Covid-19) Pandemic in Pangandaran Regency in 2021. Data collection techniques are by means of library research and filed work research, namely observations, direct observations in the field, interviews, submitting a number of questions to related parties, namely informants and documentation of documents related to the ongoing research. The source of data was obtained through direct observation to the research location and conducting direct interviews with key informants in this study, namely the Regional Government of Pangandaran Regency. Interactive model data analysis begins with data collection, data reduction, data presentation and conclusion drawing verification. The data analysis is an interactive model developed by Milles and Huberman. The results showed that the Regional Government Efforts in the Context of Preventing and Handling the Covid-19 Pandemic in Pangandaran Regency in 2021. Namely by making policies with the aim of breaking the chain of the spread of the Covid-19 virus, such as Adaptation of New Habits, Large-Scale Social Restrictions (PSBB, PPKM by staying at home, doing social distancing, and calling for compliance with health protocols. As well as conducting education and socialization both on social media including electronic media. And the most important thing is the awareness of all parties to continue to obey and discipline the protocol health services such as using masks, physical distancing and always washing hands after activities. As well as the synergy here, apart from cross-sectoral also across local governments, by coordinating and joint handling steps. After integrated coordination, it is necessary to build a complaint system that becomes a handling control tool and Covid-19 as well as a medium of communication between citizens and service providers.